Conduction Disorders After Transcatheter Aortic Valve Implantation: Evolution Over Time and Association With Long-Term Outcomes - Chua, Aileen Paula; Myagmardorj, Rinchyenkhand; Nabeta, Takeru; Kuneman, Jurrien H.; van der Kley; Frank; Bax, Jeroen J.; Ajmone Marsan, Nina (Elsevier BV, 2025)
Background: Expanding indications for transcatheter aortic valve implantation (TAVI) highlighted the importance of complications such as new left bundle branch block (LBBB) or permanent pacemaker (PPM) implantation. However, studies on the long-term outcomes of these conduction abnormalities (CA) are limited. This study aims to examine the progression of CA within the first year after TAVI and their long-term prognostic value.
Methods: TAVI patients were divided into 1) PPM implantation within the first year, 2) post-TAVI LBBB persisting until 1 year (permanent LBBB), and 3) no-CA. Endpoint was all-cause mortality after 1 year.
Results: Among 794 patients initially included, 30% developed new LBBB, which persisted in 17% until discharge; 12% received a PPM during the hospitalization. One-year follow-up was available in 502 patients: 11% were classified as permanent LBBB (n = 56), 18% as PPM (n = 89), and the rest as no-CA (n = 357). Baseline characteristics were comparable, except for valve type, with self-expanding more common among the PPM group. At 1-year follow-up, lower left ventricular ejection fraction and global longitudinal strain were observed in the PPM and permanent LBBB groups compared to the no-CA group (55% ± 9% and 15% ± ​4% vs. 54% ± 11% and 15% ± 4% vs. 58% ± 9% and 17% ± ​4%, respectively, p ​< 0.001). At long-term follow-up (median: 4 [interquartile range: 3-6] years), higher mortality was observed in the PPM group (ꭓ2 = 10.168, p = 0.006). In addition, PPM implantation (hazard ratio: 1.654, p = 0.011) and global longitudinal strain at 1 year (hazard ratio: 0.950, p = 0.027), as well as pre-TAVI EuroSCORE II and New York Heart Association III-IV at 1 year, were independently associated with the outcome.
Conclusions: Post-TAVI CAs are dynamic within the first year. Patients who needed PPM implantation did not show significant improvement in left ventricular function after TAVI and had higher long-term mortality.